Analisis Kinerja Simpang Bersinyal Pada Jalan Yos Sudarso – Jalan Galaxy Kota Palangka Raya - Ferry Dacosta Baboe; Murniati; Robby (Jurnal Serambi Engineering, 2024)
The intersection of Jl. Yos Sudarso - Jl. Galaxy is a 3-phase intersection with commercial land use, so on several approaches there are side obstacles in the form of parked vehicles that prevent road users from crossing the intersection, causing frequent queues. The aim of this research is to find out how the signalised junction is performing and to provide alternative applications so that the junction can operate optimally. This data collection is then used in the analysis to determine the performance of the junction using the Indonesian Road Capacity Manual (MKJI 1997). The results obtained from the research show that the performance of the signalised intersection Jl. Yos Sudarso - Jl. Galaxy for the existing conditions is in the ITP F category with a value of the average intersection delay = 258 smp / sec, the value of the degree of saturation on the south approach = 1.377, on the east approach = 0.663 and on the west approach = 0.893. The degree of saturation exceeds the value recommended by MKJI, which is <0.85. On the basis of this study, the recommended solution is to change the 3-phase arrangement to 2-phase and to prohibit right turns on the western approach, as well as to rearrange the time in the intersection traffic cycle at the intersection of Jl. Yos Sudarso - Jl. Galaxy in order to achieve the ITP (C) value.